Competencies required for the performance of primary health care managers: a systematic review - Katherine Soto-Schulz; Raúl Herrera-Echenique; Rodrigo Brito-Díaz; Nuria Pérez-Romero (Cadernos de Saúde Pública)
Abstract: This study aimed to identify the competencies required by primary health care managers for the effective performance of their functions. A systematic review was conducted according to PRISMA, in the databases PubMed, Scopus, Web of Science, and CINAHL, up to May 2023, in the last 10 years. The inclusion criteria were quantitative, qualitative, or mixed studies that evaluated the competencies required for primary health care managers and published in English, Spanish, or Portuguese. Methodological quality was assessed using the Mixed Methods Appraisal Tool. This article identified 171 studies, including six to the analysis. The importance of leadership, teamwork, and communication was highlighted. Furthermore, the need for disciplinary training in the health area, knowledge in administration, and use of management indicators, as well as an autonomous and flexible attitude to challenges were highlighted. The evaluation of methodological quality showed an overall good performance, except for some studies that do not report sufficient information to determine sample representativeness. Primary health care managers must possess specific competencies to effectively perform their roles, given the relevance of primary care in each country’s health system. This study provides a general framework of the required competencies for managerial responsibilities in this area. However, it is necessary to consider the particularities and local contexts of each center to develop managerial profiles adapted to their specific needs.